Getting a grip on collective cell migration - Das, Tamal; Spatz, Joachim P. (Nature cell biology, 2016)
Many cell types in our body move in a collective manner, which requires individual cells to align their movements relative to that of their neighbours. A mechanism is now described in which cadherin-rich protrusions are extended from leading migrating cells and engulfed by follower cells to guide collective migration.
Gesehen am 06.05.2020